Brain Functioning as the Ground for Spiritual Experiences and Ethical Behavior. - Travis, Fred (FBI Law Enforcement Bulletin, 2009)
Part of a special issue on ensuring the mental, physical, and spiritual health of first responders. Spiritual experiences can have a beneficial effect on brain functioning. Brain functioning transforms sensations into perceptions and thoughts into actions, and reverberations in brain circuits result in conscious experience and also structurally alter the brain. Stressful experiences modify regions of the brain involved in memory and emotions, thereby impairing memory and heightening anxiety and aggression. Furthermore, spiritual experiences change frontal executive regions, causing these areas to become more coherent and thereby producing more effective thinking and planning. Higher frontal coherence is also associated with higher moral reasoning, greater emotional stability, and reduced anxiety. In addition, as they stimulate executive brain circuits to buffer the negative impact of noxious experiences, spiritual experiences could contribute to better well-being.